TPU / PAN nano-composite film for removing PFAS in water and preparation method of TPU / PAN nano-composite film

By in situ doping and surface loading of TFN-crosslinked β-CD in the TPU/PAN nanocomposite membrane, a nanocomposite membrane with an interpenetrating network IPN structure is formed, which solves the problems of low removal efficiency of long-chain and short-chain PFAS in the prior art, and achieves an efficient and low-cost PFAS removal effect.

CN120115027AActive Publication Date: 2025-06-10UNIV OF SCI & TECH OF CHINA
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510608859.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-13
Publication Date
2025-06-10
Estimated Expiration
2045-05-13

AI Technical Summary

Technical Problem

The prior art has problems such as low efficiency when removing long-chain PFAS and short-chain PFAS in water, especially the removal efficiency of short-chain PFAS is low, and the operating pressure is high and the energy consumption cost is unbearable.

Method used

TPU/PAN nanocomposite film was used to prepare in situ doped and cross-linked β-CDs with TFN-loaded surface load by electrospinning to form a nanocomposite film with an interpenetrating network IPN structure to improve the adsorption capacity of PFAS.

Benefits of technology

The efficient removal of PFOA, PFOS and PFBA was achieved, achieving adsorption removal rates of ≥97%, ≥96% and ≥93% respectively, reducing operating pressure and energy consumption costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a TPU / PAN nano composite membrane for removing PFAS in water and a preparation method of the TPU / PAN nano composite membrane. The preparation method of the TPU / PAN nano composite membrane for removing PFAS in water comprises the following steps: adding TFN cross-linked beta-CD into TPU and PAN solutions, then carrying out electrostatic spinning to form a membrane, and then loading the TFN cross-linked beta-CD to obtain the TPU / PAN nano composite membrane. By adjusting the compounding proportion of TPU and PAN, the crosslinking degree of TFN crosslinking beta-CD and the combined action of in-situ doping and surface loading, the finally obtained TPU / PAN nano composite film has excellent PFAS adsorption removal rate, the PFOA adsorption removal rate is larger than or equal to 97%, the PFOS adsorption removal rate is larger than or equal to 96%, the PFBA adsorption removal rate is larger than or equal to 93%, and selective adsorption of long-chain PFAS and short-chain PFAS is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of preparation of nanocomposite membranes, and particularly relates to a TPU / PAN nanocomposite membrane for removing PFAS in water and a preparation method thereof. Background Art

[0002] Per- and polyfluoroalkyl substances (PFAS) are a class of synthetic fluorinated organic compounds. Due to their unique hydrophobic, oleophobic and chemical stability, they are widely used in industrial production and consumer products such as fire-fighting foams, non-stick coatings, and waterproof fabrics. However, the C-F bond energy of PFAS substances is extremely high (about 485 kJ / mol), resulting in their difficulty in degradation in the natural environment, and they are persistent, bioaccumulative and toxic. Among them, long-chain PFAS (such as PFOA, PFOS, carbon chain length ≥ C8) have been listed as priority control substances in many countries due to their extensive historical applications; while short-chain PFAS (such as PFBA, PFBS, carbon chain length ≤ C6) are widely used as long-chain substitutes, but their higher water solubility and stronger mobility lead to easier diffusion through water bodies, further expanding the pollution range. Research shows that PFAS can enter the human body through drinking water, food chains and other channels. Long-term exposure to trace amounts of PFAS (at the ng / L level) can pose health risks such as endocrine disruption, immunosuppression, and carcinogenesis to the human body. Currently, PFAS pollution has spread to water bodies, soil and organisms globally, and there is an urgent need for efficient removal technologies to ensure water quality safety.

[0003] Currently, the mainstream PFAS removal technologies include adsorption, advanced oxidation and membrane separation methods, but there are significant differences in their removal efficiencies for long- and short-chain PFAS.

[0004] Adsorption method: The adsorption removal rates of activated carbon and ion exchange resins for long-chain PFAS (such as PFOA, PFOS) can reach 90%, but the adsorption efficiency for short-chain PFAS (such as PFBA) drops sharply to less than 30%, and it is easily affected by competitive adsorption of organic matters in water. The regeneration cost is high and it is prone to cause secondary pollution.

[0005] Advanced oxidation method: Electrochemical, photocatalytic and other technologies can destroy the structure of PFAS through free radical reactions, but the degradation efficiency for short-chain PFAS (such as PFBA) is generally less than 50%, and the degradation of long-chain PFAS may generate short-chain intermediates with stronger toxicity.

[0006] Membrane separation method: The rejection rates of reverse osmosis (RO) membranes for both long- and short-chain PFAS are > 90%, but the operating pressure is high (1.5 - 7.0 MPa), and the energy consumption cost is unbearable; although nanofiltration (NF) membranes can operate at a lower pressure (0.5 - 1.5 MPa), the rejection rate for short-chain PFAS with a molecular weight < 500 Da is less than 60%.

[0007] Therefore, in view of the problems existing in the prior art, it is urgent to develop a membrane material and its preparation method with high removal rates for both long-chain PFAS and short-chain PFAS in water. Summary of the Invention

[0008] In view of the defects existing in the above prior art, an object of the present invention is to provide a preparation method of a TPU / PAN nanocomposite membrane for removing PFAS substances in water, aiming to provide a nanocomposite membrane material with high removal rates for both long-chain PFAS and short-chain PFAS in water.

[0009] To achieve the above object, the technical solution adopted by the present invention is as follows: A TPU / PAN nanocomposite membrane for removing PFAS in water comprises the following preparation steps: S1. Prepare β-cyclodextrin-tetrafluoroterephthalonitrile polymer (β-CD-TFN polymer): In an inert gas, β-cyclodextrin, tetrafluoroterephthalonitrile TFN and potassium carbonate are subjected to a polymerization reaction in DMF, followed by washing, filtering and drying to obtain it; S2. Electrospinning to prepare a TPU / PAN membrane with in-situ doped β-CD-TFN polymer: The DMF dispersion of the β-CD-TFN polymer is added to the TPU / PAN mixed solution, and after high-speed stirring to obtain a homogeneous solution, the TPU / PAN membrane is prepared by electrospinning; S3. Prepare a TPU / PAN nanocomposite membrane loaded with β-CD-TFN polymer: The TPU / PAN membrane with in-situ doped β-CD-TFN polymer obtained in S2 is added to the DMF dispersion of the β-CD-TFN polymer, stirred evenly, and then filtered, washed and dried to obtain the TPU / PAN nanocomposite membrane.

[0010] Preferably, in the step S1, the weight ratio of β-cyclodextrin / tetrafluoroterephthalonitrile / potassium carbonate is (3 - 5):1:(4 - 6); the polymerization reaction temperature is 85 - 95 °C, and the reaction time is 12 - 18 h; Preferably, the inert gas is a nitrogen atmosphere or an argon atmosphere; Preferably, the washing is carried out by washing with hydrochloric acid 3 times first, and then washing with deionized water 3 times; the drying temperature is 80 - 100 °C, and the drying time is 2 - 3 h.

[0011] Preferably, the DMF dispersion of the β-CD-TFN polymer in the step S2 is obtained by adding the β-CD-TFN polymer to DMF, stirring and swelling, and then treating with an ultrasonic crusher; Preferably, the mass concentration of the β-CD-TFN polymer in DMF is 15%-20%; Preferably, the stirring and swelling is carried out at a temperature of 60-80°C and for a time of 6-8h; Preferably, the power of the ultrasonic crusher is 300-500W, the frequency is 40-60kHZ, and the processing time is 30-60min; Preferably, the TPU / PAN mixed solution is obtained by dissolving TPU and PAN in a mixed solvent of DMF and acetone and stirring to dissolve; Preferably, the stirring and dissolving temperature is room temperature stirring, and the stirring time is magnetic stirring for 6-10 hours; Preferably, the volume ratio of DMF to acetone is 3:1; Preferably, the mass concentration of TPU / PAN in the mixed solvent is 15-25wt%; Preferably, the mass ratio of TPU to PAN is (2-3): 1; Preferably, the high-speed stirring time is 30-60 min, and the stirring rate is 8000-1000 rpm; Preferably, in step S2, the β-CD-TFN polymer accounts for 5-15% of the total mass of TPU and PAN; Preferably, the electrospinning method comprises the following specific steps: electrospinning is performed using an electrospinning device, the homogeneous solution is first injected into a plastic syringe, the spinning conditions are: voltage 15 kV, injection speed 0.5 mL / h-1 mL / h, receiving distance 10 cm-20 cm, continuous spinning for 1-3 h, that is, a TPU / PAN film in situ doped with β-CD-TFN polymer is obtained on a collecting roller; Preferably, in step S3, the β-CD-TFN polymer accounts for 5-15% of the total mass of TPU and PAN; Preferably, the DMF dispersion of the β-CD-TFN polymer in step S3 is obtained by placing the β-CD-TFN polymer in DMF, stirring and swelling it, and then treating it with an ultrasonic crusher; Preferably, the stirring and swelling temperature is 60-80°C, the time is 6-8h; the power of the ultrasonic crusher is 300-500W, the frequency is 40-60kHZ, and the processing time is 30-60min; Preferably, the filtration is vacuum filtration; the washing is ethanol washing; Preferably, the drying is carried out at 50-60° C. for 8-12 hours.

[0012] The second object of the present invention is to provide a TPU / PAN nanocomposite membrane for removing PFAS from water, which is prepared by the aforementioned preparation method.

[0013] The adsorption and removal rate of the TPU / PAN nanocomposite membrane for removing PFAS in water for PFOA is ≥97%, for PFOS is ≥96%, and for PFBA is ≥93%.

[0014] The third object of the present invention is to provide an application of the TPU / PAN nanocomposite membrane prepared by the foregoing preparation method, and the application is to remove PFAS substances in water.

[0015] Compared with the prior art, the present invention has the following advantages: (1) In the preparation method of the TPU / PAN nanocomposite membrane for removing PFAS in water, the present invention creatively uses TPU and PAN as the base membranes for preparing the nanocomposite membrane. Utilizing the differences in the flexibility of the molecular chains and the molecular weights of the two, they are entangled with each other in the system to form an interpenetrating network IPN structure, presenting a nanocomposite membrane base membrane with different pore sizes. Then, β-CD crosslinked by TFN is in-situ doped therein. While introducing cyclodextrin with adsorption function into the base membrane structure, a TPU / PAN membrane with hydrophobic effect is obtained. Finally, β-CD crosslinked by TFN is loaded on the surface of the TPU / PAN membrane to obtain the TPU / PAN nanocomposite membrane, so that the finally obtained TPU / PAN nanocomposite membrane has excellent adsorption capacity for long-chain PFAS and short-chain PFAS.

[0016] (2) The present invention creatively uses TPU and PAN with a specific ratio compounding as the base membranes of the nanocomposite membrane. While forming the IPN network, they play a synergistic effect, bringing an interpenetrating network structure with different pore sizes and adsorption capacities in the system, so that the finally obtained nanocomposite membrane has good selective adsorption for long-chain PFAS and short-chain PFAS.

[0017] (3) The present invention creatively selects to in-situ dope and surface load β-CD crosslinked by TFN in the TPU / PAN nanocomposite membrane, and the two play a synergistic effect. On the one hand, the β-CD after TFN crosslinking forms continuous cyclodextrin cavities, and on the other hand, fluorinated hydrophobic chain segments are introduced, increasing the adsorption capacity for PFAS. At the same time, the hydroxyl groups in the in-situ doped crosslinked β-CD can further form crosslinks with the residual isocyanate in the TPU, and form strong interactions with amino groups and cyano groups, jointly improving the adsorption capacity for PFAS.

[0018] (4) The finally obtained TPU / PAN nanocomposite membrane for removing PFAS in water can achieve an adsorption and removal rate of ≥97% for PFOA, ≥96% for PFOS, and ≥93% for PFBA. Detailed implementation manners

[0019] Unless otherwise specified, the raw materials and equipment used in the present invention are common raw materials and equipment in the art; the methods used in the present invention are conventional methods in the art unless otherwise specified.

[0020] Unless otherwise specified, the meanings of the terms in this specification are the same as those generally understood by those skilled in the art. However, in case of conflict, the definitions in this specification shall prevail.

[0021] To better illustrate the purpose, technical solution and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0022] The raw materials are selected as follows: TPU: BASF, Konz 208 / F; PAN: Shanghai Merryer Biochemical Technology Co., Ltd., MERYER, M39436; β-cyclodextrin: Shanghai Aladdin Biochemical Technology Co., Ltd., C104384; β-cyclodextrin-tetrafluoroterephthalonitrile polymer (β-CD-TFN polymer): Preparation Example 1 In a nitrogen atmosphere, β-cyclodextrin, tetrafluoroterephthalonitrile TFN and potassium carbonate were subjected to a polymerization reaction in DMF at 85 °C for 18 h. After washing three times with hydrochloric acid first and then three times with deionized water, filtration was carried out, and drying was carried out at 95 °C for 3 h to obtain the β-CD-TFN polymer, abbreviated as β-CD-TFN-1; Among them, the weight ratio of β-cyclodextrin / tetrafluoroterephthalonitrile / potassium carbonate is 3:1:4.

[0023] Preparation Example 2 In a nitrogen atmosphere, β-cyclodextrin, tetrafluoroterephthalonitrile TFN and potassium carbonate were subjected to a polymerization reaction in DMF at 85 °C for 18 h. After washing three times with hydrochloric acid first and then three times with deionized water, filtration was carried out, and drying was carried out at 95 °C for 3 h to obtain the β-CD-TFN polymer, abbreviated as β-CD-TFN-2; Among them, the weight ratio of β-cyclodextrin / tetrafluoroterephthalonitrile / potassium carbonate is 5:1:4.

[0024] Comparative Preparation Example 1 In a nitrogen atmosphere, β-cyclodextrin, tetrafluoroterephthalonitrile TFN and potassium carbonate were subjected to a polymerization reaction in DMF at 85 °C for 18 h. After washing three times with hydrochloric acid first and then three times with deionized water, filtration was carried out, and drying was carried out at 95 °C for 3 h to obtain the β-CD-TFN polymer, abbreviated as β-CD-TFN-c1; Among them, the weight ratio of β-cyclodextrin / tetrafluoroterephthalonitrile / potassium carbonate is 2:1:4.

[0025] Comparative Preparation Example 2 In a nitrogen atmosphere, β-cyclodextrin, tetrafluoroterephthalonitrile (TFN), and potassium carbonate were subjected to a polymerization reaction in DMF at 85 °C for 18 h. After washing three times with hydrochloric acid and then three times with deionized water, filtration was carried out, and drying was performed at 95 °C for 3 h to obtain the β-CD-TFN polymer, abbreviated as β-CD-TFN-c2; Among them, the weight ratio of β-cyclodextrin / tetrafluoroterephthalonitrile / potassium carbonate is 6:1:4.

[0026] Example 1

[0027] A TPU / PAN nanocomposite membrane for removing PFAS in water, comprising the following preparation steps: S1. Prepare β-CD-TFN-1 according to Preparation Example 1; S2. Electrospinning to prepare a TPU / PAN membrane with in-situ doped β-CD-TFN-1: β-CD-TFN-1 was added to DMF and stirred and swollen at 60 °C for 8 h, and then treated with an ultrasonic crusher (power: 500 W, frequency: 60 kHz) for 30 min to obtain a DMF dispersion of β-CD-TFN-1; among them, the mass concentration of β-CD-TFN-1 in DMF is 15%; TPU and PAN were dissolved in a mixed solvent of DMF and acetone with a volume ratio of 3:1 and magnetically stirred at room temperature for 10 h to obtain a TPU / PAN mixed solution; among them, the mass concentration of TPU / PAN in the mixed solvent is 15%, and the mass ratio of TPU and PAN is 2:1; The DMF dispersion of β-CD-TFN-1 was added to the TPU / PAN mixed solution, stirred at 10000 rpm for 60 min to obtain a homogeneous solution, and then an in-situ doped β-CD-TFN-1 TPU / PAN membrane was prepared by electrospinning; among them, β-CD-TFN-1 accounts for 5% of the total mass of TPU and PAN; The specific steps of the electrospinning method are as follows: Electrospinning was carried out using an electrospinning device. First, the homogeneous solution was injected into a plastic syringe, and the spinning conditions were: voltage 15 kV, injection speed 0.5 mL / h, receiving distance 10 cm, and continuous spinning for 2 h, and an in-situ doped β-CD-TFN-1 TPU / PAN membrane was obtained on the collecting roller; S3. Prepare a TPU / PAN nanocomposite membrane loaded with β-CD-TFN-1: After adding β-CD-TFN-1 to DMF and stirring and swelling at 60 °C for 8 h, it was treated with an ultrasonic crusher (power 500 W, frequency 60 kHz) for 30 min to obtain a DMF dispersion of β-CD-TFN-1; among them, the mass concentration of β-CD-TFN-1 in DMF was 15%; among them, β-CD-TFN-1 accounted for 5% of the total mass of TPU and PAN.

[0028] The in-situ doped β-CD-TFN-1 TPU / PAN film obtained in S2 was put into the DMF dispersion of β-CD-TFN-1, stirred evenly, then vacuum filtered, washed with ethanol 3 times, and dried at 60 °C for 8 h to obtain a TPU / PAN nanocomposite film.

[0029] Example 2

[0030] A TPU / PAN nanocomposite film for removing PFAS in water, comprising the following preparation steps: S1. Prepare β-CD-TFN-1 according to Preparation Example 1; S2. Electrospinning to prepare an in-situ doped β-CD-TFN-1 TPU / PAN film: After adding β-CD-TFN-1 to DMF and stirring and swelling at 60 °C for 8 h, it was treated with an ultrasonic crusher (power 500 W, frequency 60 kHz) for 30 min to obtain a DMF dispersion of β-CD-TFN-1; among them, the mass concentration of β-CD-TFN-1 in DMF was 15%; Dissolve TPU and PAN in a mixed solvent of DMF and acetone with a volume ratio of 3:1 and magnetically stir at room temperature for 10 h to obtain a TPU / PAN mixed solution; among them, the mass concentration of TPU / PAN in the mixed solvent was 15%, and the mass ratio of TPU and PAN was 3:1; Add the DMF dispersion of β-CD-TFN-1 to the TPU / PAN mixed solution, stir at 10000 rpm for 60 min to obtain a homogeneous solution, and then use electrospinning to prepare an in-situ doped β-CD-TFN-1 TPU / PAN film; among them, β-CD-TFN-1 accounted for 5% of the total mass of TPU and PAN; The specific steps of the electrospinning method are as follows: Electrospinning is carried out using an electrospinning device. First, inject the homogeneous solution into a plastic syringe. The electrospinning conditions are: voltage 15 kV, injection speed 0.5 mL / h, receiving distance 10 cm, and continuous electrospinning for 2 h, that is, an in-situ doped β-CD-TFN-1 TPU / PAN film is obtained on the collection roller; S3. Prepare a TPU / PAN nanocomposite film loaded with β-CD-TFN-1: After adding β-CD-TFN-1 into DMF and stirring and swelling at 60 °C for 8 h, it was treated with an ultrasonic crusher (power: 500 W, frequency: 60 kHz) for 30 min to obtain a DMF dispersion of β-CD-TFN-1; wherein, the mass concentration of β-CD-TFN-1 in DMF was 15%; wherein, β-CD-TFN-1 accounted for 5% of the total mass of TPU and PAN.

[0031] The in-situ doped TPU / PAN membrane with β-CD-TFN-1 obtained in S2 was put into the DMF dispersion of β-CD-TFN-1, stirred evenly, then vacuum filtered, washed with ethanol three times, and dried at 60 °C for 8 h to obtain the TPU / PAN nanocomposite membrane.

[0032] Example 3

[0033] A TPU / PAN nanocomposite membrane for removing PFAS in water, comprising the following preparation steps: S1. Prepare β-CD-TFN-1 according to Preparation Example 1; S2. Electrospinning to prepare an in-situ doped TPU / PAN membrane with β-CD-TFN-1: After adding β-CD-TFN-1 into DMF and stirring and swelling at 60 °C for 8 h, it was treated with an ultrasonic crusher (power: 500 W, frequency: 60 kHz) for 30 min to obtain a DMF dispersion of β-CD-TFN-1; wherein, the mass concentration of β-CD-TFN-1 in DMF was 15%; Dissolve TPU and PAN in a mixed solvent of DMF and acetone with a volume ratio of 3:1 and magnetically stir at room temperature for 10 h to obtain a TPU / PAN mixed solution; wherein, the mass concentration of TPU / PAN in the mixed solvent was 15%, and the mass ratio of TPU to PAN was 3:1; Add the DMF dispersion of β-CD-TFN-1 into the TPU / PAN mixed solution, stir at 10000 rpm for 60 min to obtain a homogeneous solution, and then use the electrospinning method to prepare an in-situ doped TPU / PAN membrane with β-CD-TFN-1; wherein, β-CD-TFN-1 accounted for 10% of the total mass of TPU and PAN; The specific steps of the electrospinning method are as follows: Use an electrospinning device for electrospinning. First, inject the homogeneous solution into a plastic syringe. The spinning conditions are: voltage 15 kV, injection speed 0.5 mL / h, receiving distance 10 cm, and continuous spinning for 2 h, that is, an in-situ doped TPU / PAN membrane with β-CD-TFN-1 is obtained on the collecting roller; S3. Prepare a TPU / PAN nanocomposite membrane loaded with β-CD-TFN-1: β-CD-TFN-1 was added to DMF and stirred at 60 °C for 8 h to swell, and then treated with an ultrasonic crusher (power: 500 W, frequency: 60 kHz) for 30 min to obtain a DMF dispersion of β-CD-TFN-1. Among them, the mass concentration of β-CD-TFN-1 in DMF was 15%. Among them, β-CD-TFN-1 accounted for 5% of the total mass of TPU and PAN.

[0034] The in-situ doped β-CD-TFN-1 TPU / PAN membrane obtained in S2 was put into the DMF dispersion of β-CD-TFN-1, stirred evenly, then vacuum filtered, washed with ethanol three times, and dried at 60 °C for 8 h to obtain a TPU / PAN nanocomposite membrane.

[0035] Example 4

[0036] A TPU / PAN nanocomposite membrane for removing PFAS in water, comprising the following preparation steps: S1. Prepare β-CD-TFN-1 according to Preparation Example 1; S2. Electrospinning to prepare an in-situ doped β-CD-TFN-1 TPU / PAN membrane: β-CD-TFN-1 was added to DMF and stirred at 60 °C for 8 h to swell, and then treated with an ultrasonic crusher (power: 500 W, frequency: 60 kHz) for 30 min to obtain a DMF dispersion of β-CD-TFN-1. Among them, the mass concentration of β-CD-TFN-1 in DMF was 15%; TPU and PAN were dissolved in a mixed solvent of DMF and acetone with a volume ratio of 3:1 and magnetically stirred at room temperature for 10 h to obtain a TPU / PAN mixed solution. Among them, the mass concentration of TPU / PAN in the mixed solvent was 15%, and the mass ratio of TPU and PAN was 3:1; The DMF dispersion of β-CD-TFN-1 was added to the TPU / PAN mixed solution, stirred at 10000 rpm for 60 min to obtain a homogeneous solution, and then an in-situ doped β-CD-TFN-1 TPU / PAN membrane was prepared by electrospinning. Among them, β-CD-TFN-1 accounted for 5% of the total mass of TPU and PAN; The specific steps of the electrospinning method are as follows: Electrospinning was carried out using an electrospinning device. First, the homogeneous solution was injected into a plastic syringe. The spinning conditions were: voltage 15 kV, injection speed 0.5 mL / h, receiving distance 10 cm, and continuous spinning for 2 h, and an in-situ doped β-CD-TFN-1 TPU / PAN membrane was obtained on the collecting roller; S3. Prepare a TPU / PAN nanocomposite membrane loaded with β-CD-TFN-1: β-CD-TFN-1 was added to DMF and stirred at 60 °C for 8 h for swelling. After that, it was treated with an ultrasonic crusher (power: 500 W, frequency: 60 kHz) for 30 min to obtain a DMF dispersion of β-CD-TFN-1. Among them, the mass concentration of β-CD-TFN-1 in DMF was 15%; among them, β-CD-TFN-1 accounted for 10% of the total mass of TPU and PAN.

[0037] The in-situ doped TPU / PAN membrane with β-CD-TFN-1 obtained in S2 was put into the DMF dispersion of β-CD-TFN-1. After stirring evenly, it was vacuum filtered, washed with ethanol three times, and dried at 60 °C for 8 h to obtain a TPU / PAN nanocomposite membrane.

[0038] Example 5

[0039] A TPU / PAN nanocomposite membrane for removing PFAS in water, comprising the following preparation steps: S1. Prepare β-CD-TFN-2 according to Preparation Example 2; S2. Electrospinning to prepare an in-situ doped TPU / PAN membrane with β-CD-TFN-2: β-CD-TFN-2 was added to DMF and stirred at 60 °C for 8 h for swelling. After that, it was treated with an ultrasonic crusher (power: 500 W, frequency: 60 kHz) for 30 min to obtain a DMF dispersion of β-CD-TFN-2. Among them, the mass concentration of β-CD-TFN-2 in DMF was 15%; TPU and PAN were dissolved in a mixed solvent of DMF and acetone with a volume ratio of 3:1 and magnetically stirred at room temperature for 10 h to obtain a TPU / PAN mixed solution. Among them, the mass concentration of TPU / PAN in the mixed solvent was 15%, and the mass ratio of TPU and PAN was 3:1; The DMF dispersion of β-CD-TFN-2 was added to the TPU / PAN mixed solution, stirred at 10000 rpm for 60 min to obtain a homogeneous solution, and then an in-situ doped TPU / PAN membrane with β-CD-TFN-2 was prepared by electrospinning. Among them, β-CD-TFN-2 accounted for 5% of the total mass of TPU and PAN; The specific steps of the electrospinning method are as follows: Electrospinning was carried out using an electrospinning device. First, the homogeneous solution was injected into a plastic syringe. The spinning conditions were: voltage 15 kV, injection speed 0.5 mL / h, receiving distance 10 cm, and continuous spinning for 2 h, and an in-situ doped TPU / PAN membrane with β-CD-TFN-2 was obtained on the collecting roller; S3. Prepare a TPU / PAN nanocomposite membrane loaded with β-CD-TFN-2: β-CD-TFN-2 was added to DMF and stirred at 60 °C for 8 h to swell, and then treated with an ultrasonic crusher (power: 500 W, frequency: 60 kHz) for 30 min to obtain a DMF dispersion of β-CD-TFN-2; wherein, the mass concentration of β-CD-TFN-2 in DMF was 15%; wherein, β-CD-TFN-2 accounted for 5% of the total mass of TPU and PAN.

[0040] The in-situ doped TPU / PAN membrane with β-CD-TFN-2 obtained in S2 was put into the DMF dispersion of β-CD-TFN-2, stirred evenly, vacuum filtered, washed with ethanol three times, and dried at 60 °C for 8 h to obtain a TPU / PAN nanocomposite membrane.

[0041] Example 6

[0042] A TPU / PAN nanocomposite membrane for removing PFAS in water, comprising the following preparation steps: S1. Prepare β-CD-TFN-2 according to Preparation Example 2; S2. Electrospinning to prepare an in-situ doped TPU / PAN membrane with β-CD-TFN-2: β-CD-TFN-2 was added to DMF and stirred at 60 °C for 8 h to swell, and then treated with an ultrasonic crusher (power: 500 W, frequency: 60 kHz) for 30 min to obtain a DMF dispersion of β-CD-TFN-2; wherein, the mass concentration of β-CD-TFN-2 in DMF was 15%; TPU and PAN were dissolved in a mixed solvent of DMF and acetone with a volume ratio of 3:1 and magnetically stirred at room temperature for 10 h to obtain a TPU / PAN mixed solution; wherein, the mass concentration of TPU / PAN in the mixed solvent was 15%, and the mass ratio of TPU and PAN was 3:1; The DMF dispersion of β-CD-TFN-2 was added to the TPU / PAN mixed solution, stirred at 10000 rpm for 60 min to obtain a homogeneous solution, and then an in-situ doped TPU / PAN membrane with β-CD-TFN-2 was prepared by electrospinning; wherein, β-CD-TFN-2 accounted for 5% of the total mass of TPU and PAN; The specific steps of the electrospinning method are as follows: Electrospinning was carried out using an electrospinning device. First, the homogeneous solution was injected into a plastic syringe, and the spinning conditions were: voltage 15 kV, injection speed 0.5 mL / h, receiving distance 10 cm, and continuous spinning for 2 h, and an in-situ doped TPU / PAN membrane with β-CD-TFN-2 was obtained on the collecting roller; S3. Prepare a TPU / PAN nanocomposite membrane loaded with β-CD-TFN-2: β-CD-TFN-2 was added to DMF and stirred and swollen at 60 °C for 8 h, and then treated with an ultrasonic crusher (power: 500 W, frequency: 60 kHz) for 30 min to obtain a DMF dispersion of β-CD-TFN-2; wherein, the mass concentration of β-CD-TFN-2 in DMF was 15%; wherein, β-CD-TFN-2 accounted for 10% of the total mass of TPU and PAN.

[0043] The in-situ doped TPU / PAN membrane with β-CD-TFN-2 obtained in S2 was put into the DMF dispersion of β-CD-TFN-2, stirred evenly, vacuum filtered, washed with ethanol three times, and dried at 60 °C for 8 h to obtain a TPU / PAN nanocomposite membrane.

[0044] Comparative Example 1 A TPU / PAN nanocomposite membrane for removing PFAS from water comprises the following preparation steps: S1. Prepare β-CD-TFN-c1 according to Comparative Preparation Example 1; S2. Electrospinning to prepare an in-situ doped TPU / PAN membrane with β-CD-TFN-c1: β-CD-TFN-c1 was added to DMF and stirred and swollen at 60 °C for 8 h, and then treated with an ultrasonic crusher (power: 500 W, frequency: 60 kHz) for 30 min to obtain a DMF dispersion of β-CD-TFN-c1; wherein, the mass concentration of β-CD-TFN-c1 in DMF was 15%; TPU and PAN were dissolved in a mixed solvent of DMF and acetone with a volume ratio of 3:1 and magnetically stirred at room temperature for 10 h to obtain a TPU / PAN mixed solution; wherein, the mass concentration of TPU / PAN in the mixed solvent was 15%, and the mass ratio of TPU to PAN was 3:1; The DMF dispersion of β-CD-TFN-c1 was added to the TPU / PAN mixed solution, stirred at 10000 rpm for 60 min to obtain a homogeneous solution, and then an in-situ doped TPU / PAN membrane with β-CD-TFN-c1 was prepared by electrospinning; wherein, β-CD-TFN-c1 accounted for 5% of the total mass of TPU and PAN; The specific steps of the electrospinning method are as follows: Electrospinning was carried out using an electrospinning device. First, the homogeneous solution was injected into a plastic syringe, and the spinning conditions were: voltage 15 kV, injection speed 0.5 mL / h, receiving distance 10 cm, and continuous spinning for 2 h, and an in-situ doped TPU / PAN membrane with β-CD-TFN-c1 was obtained on the collecting roller; S3. Prepare a TPU / PAN nanocomposite membrane loaded with β-CD-TFN-c1: β-CD-TFN-c1 was added to DMF and stirred at 60 °C for 8 h to swell, and then treated with an ultrasonic crusher (power: 500 W, frequency: 60 kHz) for 30 min to obtain a DMF dispersion of β-CD-TFN-c1; among them, the mass concentration of β-CD-TFN-c1 in DMF was 15%; among them, β-CD-TFN-c1 accounted for 10% of the total mass of TPU and PAN.

[0045] The in-situ doped TPU / PAN membrane with β-CD-TFN-c1 obtained in S2 was put into the DMF dispersion of β-CD-TFN-c1, stirred evenly, vacuum filtered, washed with ethanol three times, and dried at 60 °C for 8 h to obtain a TPU / PAN nanocomposite membrane.

[0046] Comparative Example 2 A TPU / PAN nanocomposite membrane for removing PFAS in water, comprising the following preparation steps: S1. Prepare β-CD-TFN-c2 according to Comparative Preparation Example 2. S2. Electrospinning to prepare an in-situ doped TPU / PAN membrane with β-CD-TFN-c2: β-CD-TFN-c2 was added to DMF and stirred at 60 °C for 8 h to swell, and then treated with an ultrasonic crusher (power: 500 W, frequency: 60 kHz) for 30 min to obtain a DMF dispersion of β-CD-TFN-c2; among them, the mass concentration of β-CD-TFN-c2 in DMF was 15%. TPU and PAN were dissolved in a mixed solvent of DMF and acetone with a volume ratio of 3:1 and magnetically stirred at room temperature for 10 h to obtain a TPU / PAN mixed solution; among them, the mass concentration of TPU / PAN in the mixed solvent was 15%, and the mass ratio of TPU and PAN was 3:1. The DMF dispersion of β-CD-TFN-c2 was added to the TPU / PAN mixed solution, stirred at 10000 rpm for 60 min to obtain a homogeneous solution, and then an in-situ doped TPU / PAN membrane with β-CD-TFN-c2 was prepared by electrospinning; among them, β-CD-TFN-c2 accounted for 5% of the total mass of TPU and PAN. The specific steps of the electrospinning method are as follows: Electrospinning was carried out using an electrospinning device. First, the homogeneous solution was injected into a plastic syringe, and the spinning conditions were: voltage 15 kV, injection speed 0.5 mL / h, receiving distance 10 cm, and continuous spinning for 2 h, and an in-situ doped TPU / PAN membrane with β-CD-TFN-c2 was obtained on the collecting roller. S3. Prepare a TPU / PAN nanocomposite membrane loaded with β-CD-TFN-c2: β-CD-TFN-c2 was added to DMF and stirred at 60 °C for 8 h to swell. After that, it was treated with an ultrasonic crusher (power: 500 W, frequency: 60 kHz) for 30 min to obtain a DMF dispersion of β-CD-TFN-c2; among them, the mass concentration of β-CD-TFN-c2 in DMF was 15%; among them, β-CD-TFN-c2 accounted for 10% of the total mass of TPU and PAN.

[0047] The in-situ doped TPU / PAN membrane with β-CD-TFN-c2 obtained in S2 was put into the DMF dispersion of β-CD-TFN-c2. After stirring evenly, it was vacuum filtered, washed with ethanol three times, and dried at 60 °C for 8 h to obtain a TPU / PAN nanocomposite membrane.

[0048] Comparative Example 3 A TPU / PAN nanocomposite membrane for removing PFAS in water, comprising the following preparation steps: S1. Prepare β-CD-TFN-1 according to Preparation Example 1; S2. Electrospinning to prepare an in-situ doped TPU / PAN membrane with β-CD-TFN-1: β-CD-TFN-1 was added to DMF and stirred at 60 °C for 8 h to swell. After that, it was treated with an ultrasonic crusher (power: 500 W, frequency: 60 kHz) for 30 min to obtain a DMF dispersion of β-CD-TFN-1; among them, the mass concentration of β-CD-TFN-1 in DMF was 15%; TPU and PAN were dissolved in a mixed solvent of DMF and acetone with a volume ratio of 3:1 and magnetically stirred at room temperature for 10 h to obtain a TPU / PAN mixed solution; among them, the mass concentration of TPU / PAN in the mixed solvent was 15%, and the mass ratio of TPU and PAN was 1:1; The DMF dispersion of β-CD-TFN-1 was added to the TPU / PAN mixed solution and stirred at 10000 rpm for 60 min to obtain a homogeneous solution. Then, an in-situ doped TPU / PAN membrane with β-CD-TFN-1 was prepared by electrospinning; among them, β-CD-TFN-1 accounted for 5% of the total mass of TPU and PAN; The specific steps of the electrospinning method are as follows: Electrospinning was carried out using an electrospinning device. First, the homogeneous solution was injected into a plastic syringe. The spinning conditions were: voltage 15 kV, injection speed 0.5 mL / h, receiving distance 10 cm, and continuous spinning for 2 h, and an in-situ doped TPU / PAN membrane with β-CD-TFN-1 was obtained on the collecting roller; S3. Prepare a TPU / PAN nanocomposite membrane loaded with β-CD-TFN-1: β-CD-TFN-1 was added to DMF and stirred at 60 °C for 8 h to swell, and then treated with an ultrasonic crusher (power: 500 W, frequency: 60 kHz) for 30 min to obtain a DMF dispersion of β-CD-TFN-1. Among them, the mass concentration of β-CD-TFN-1 in DMF was 15%. Among them, β-CD-TFN-1 accounted for 10% of the total mass of TPU and PAN.

[0049] The in-situ doped TPU / PAN membrane with β-CD-TFN-1 obtained in S2 was put into the DMF dispersion of β-CD-TFN-1, stirred evenly, then vacuum filtered, washed with ethanol three times, and dried at 60 °C for 8 h to obtain the TPU / PAN nanocomposite membrane.

[0050] Comparative Example 4 A TPU / PAN nanocomposite membrane for removing PFAS in water, comprising the following preparation steps: S1. Prepare β-CD-TFN-1 according to Preparation Example 1; S2. Electrospinning to prepare an in-situ doped TPU / PAN membrane with β-CD-TFN-1: β-CD-TFN-1 was added to DMF and stirred at 60 °C for 8 h to swell, and then treated with an ultrasonic crusher (power: 500 W, frequency: 60 kHz) for 30 min to obtain a DMF dispersion of β-CD-TFN-1. Among them, the mass concentration of β-CD-TFN-1 in DMF was 15%. TPU and PAN were dissolved in a mixed solvent of DMF and acetone with a volume ratio of 3:1 and magnetically stirred at room temperature for 10 h to obtain a TPU / PAN mixed solution. Among them, the mass concentration of TPU / PAN in the mixed solvent was 15%, and the mass ratio of TPU to PAN was 4:1. The DMF dispersion of β-CD-TFN-1 was added to the TPU / PAN mixed solution, stirred at 10000 rpm for 60 min to obtain a homogeneous solution, and then an in-situ doped TPU / PAN membrane with β-CD-TFN-1 was prepared by electrospinning. Among them, β-CD-TFN-1 accounted for 5% of the total mass of TPU and PAN. The specific steps of the electrospinning method are as follows: Electrospinning was carried out using an electrospinning device. First, the homogeneous solution was injected into a plastic syringe. The electrospinning conditions were: voltage 15 kV, injection speed 0.5 mL / h, receiving distance 10 cm, and continuous electrospinning for 2 h, and an in-situ doped TPU / PAN membrane with β-CD-TFN-1 was obtained on the collecting roller. S3. Prepare a TPU / PAN nanocomposite membrane loaded with β-CD-TFN-1: After adding β-CD-TFN-1 into DMF and stirring and swelling at 60 °C for 8 h, it was treated with an ultrasonic crusher (power: 500 W, frequency: 60 kHz) for 30 min to obtain a DMF dispersion of β-CD-TFN-1; wherein, the mass concentration of β-CD-TFN-1 in DMF was 15%; wherein, β-CD-TFN-1 accounted for 10% of the total mass of TPU and PAN.

[0051] The in-situ doped β-CD-TFN-1 TPU / PAN membrane obtained in S2 was put into the DMF dispersion of β-CD-TFN-1, stirred evenly, then vacuum filtered, washed with ethanol three times, and dried at 60 °C for 8 h to obtain a TPU / PAN nanocomposite membrane.

[0052] Comparative Example 5 A TPU / PAN nanocomposite membrane for removing PFAS in water, comprising the following preparation steps: S1. Prepare β-CD; S2. Electrospinning to prepare an in-situ doped β-CD TPU / PAN membrane: β-CD was added into DMF and stirred at 60 °C for 3 h to obtain a DMF dispersion of β-CD; wherein, the mass concentration of β-CD in DMF was 15%; TPU and PAN were dissolved in a mixed solvent of DMF and acetone with a volume ratio of 3:1 and magnetically stirred at room temperature for 10 h to obtain a TPU / PAN mixed solution; wherein, the mass concentration of TPU / PAN in the mixed solvent was 15%, and the mass ratio of TPU and PAN was 3:1; The DMF dispersion of β-CD was added into the TPU / PAN mixed solution, stirred at 10000 rpm for 60 min to obtain a homogeneous solution, and then an in-situ doped β-CD TPU / PAN membrane was prepared by electrospinning; wherein, β-CD accounted for 5% of the total mass of TPU and PAN; The specific steps of the electrospinning method were as follows: Electrospinning was carried out using an electrospinning device. First, the homogeneous solution was injected into a plastic syringe, and the electrospinning conditions were: voltage 15 kV, injection speed 0.5 mL / h, receiving distance 10 cm, and continuous electrospinning for 2 h, and an in-situ doped β-CD TPU / PAN membrane was obtained on the collecting roller; S3. Prepare a TPU / PAN nanocomposite membrane loaded with β-CD: β-CD was added into DMF and stirred at 60 °C for 3 h to obtain a DMF dispersion of β-CD; wherein, the mass concentration of β-CD in DMF was 15%; Among them, β-CD accounted for 10% of the total mass of TPU and PAN.

[0053] The in-situ doped β-CD TPU / PAN membrane obtained in S2 was placed in a DMF dispersion of β-CD, stirred evenly, then vacuum filtered, washed three times with ethanol, and dried at 60 °C for 8 h to obtain the TPU / PAN nanocomposite membrane.

[0054] Comparative Example 6 A TPU / PAN nanocomposite membrane for removing PFAS in water, comprising the following preparation steps: S1. Prepare β-CD-TFN-1 according to Preparation Example 1; S2. Electrospinning to prepare a TPU / PAN membrane: TPU and PAN were dissolved in a mixed solvent of DMF and acetone with a volume ratio of 3:1 and magnetically stirred at room temperature for 10 h to obtain a TPU / PAN mixed solution; wherein, the mass concentration of TPU / PAN in the mixed solvent was 15%, and the mass ratio of TPU to PAN was 3:1; The obtained TPU / PAN mixed solution was used to prepare a TPU / PAN membrane by electrospinning; The specific steps of the electrospinning method are as follows: Electrospinning was carried out using an electrospinning device. First, the homogeneous solution was injected into a plastic syringe. The spinning conditions were: voltage 15 kV, injection speed 0.5 mL / h, receiving distance 10 cm, and continuous spinning for 2 h, and the TPU / PAN membrane was obtained on the collecting roller; S3. Prepare a TPU / PAN nanocomposite membrane loaded with β-CD-TFN-1: β-CD-TFN-1 was added to DMF and stirred and swollen at 60 °C for 8 h, and then treated with an ultrasonic crusher (power 500 W, frequency 60 kHz) for 30 min to obtain a DMF dispersion of β-CD-TFN-1; wherein, the mass concentration of β-CD-TFN-1 in DMF was 15%; wherein, β-CD-TFN-1 accounted for 15% of the total mass of TPU and PAN.

[0055] The TPU / PAN membrane obtained in S2 was placed in a DMF dispersion of β-CD-TFN-1, stirred evenly, then vacuum filtered, washed three times with ethanol, and dried at 60 °C for 8 h to obtain the TPU / PAN nanocomposite membrane.

[0056] Comparative Example 7 A TPU / PAN nanocomposite membrane for removing PFAS in water, comprising the following preparation steps: S1. Prepare β-CD-TFN-1 according to Preparation Example 1; S2. Electrospinning to prepare an in-situ doped β-CD-TFN-1 TPU / PAN membrane: β-CD-TFN-1 was added to DMF and stirred at 60 °C for 8 h for swelling, and then treated with an ultrasonic crusher (power: 500 W, frequency: 60 kHz) for 30 min to obtain a DMF dispersion of β-CD-TFN-1; among them, the mass concentration of β-CD-TFN-1 in DMF was 15%; TPU and PAN were dissolved in a mixed solvent of DMF and acetone with a volume ratio of 3:1 and magnetically stirred at room temperature for 10 h to obtain a TPU / PAN mixed solution; among them, the mass concentration of TPU / PAN in the mixed solvent was 15%, and the mass ratio of TPU to PAN was 4:1; The DMF dispersion of β-CD-TFN-1 was added to the TPU / PAN mixed solution, and stirred at 10000 rpm for 60 min to obtain a homogeneous solution, and then an electrospinning method was used to prepare a TPU / PAN membrane in-situ doped with β-CD-TFN-1; among them, β-CD-TFN-1 accounted for 15% of the total mass of TPU and PAN; The specific steps of the electrospinning method were as follows: electrospinning was carried out using an electrospinning device. First, the homogeneous solution was injected into a plastic syringe, and the spinning conditions were: voltage 15 kV, injection speed 0.5 mL / h - 1 mL / h, receiving distance 10 cm - 20 cm, and continuous spinning for 1 - 3 h, and a TPU / PAN membrane in-situ doped with β-CD-TFN-1 was obtained on the collecting roller; S3. Preparation of TPU / PAN nanocomposite membrane: The TPU / PAN membrane in-situ doped with β-CD-TFN-1 obtained in S2 was dried at 60 °C for 8 h to obtain a TPU / PAN nanocomposite membrane.

[0057] Comparative Example 8 A TPU nanocomposite membrane for removing PFAS in water, comprising the following preparation steps: S1. Prepare β-CD-TFN-1 according to Preparation Example 1; S2. Electrospinning to prepare a TPU membrane in-situ doped with β-CD-TFN-1: β-CD-TFN-1 was added to DMF and stirred at 60 °C for 8 h for swelling, and then treated with an ultrasonic crusher (power: 500 W, frequency: 60 kHz) for 30 min to obtain a DMF dispersion of β-CD-TFN-1; among them, the mass concentration of β-CD-TFN-1 in DMF was 15%; TPU was dissolved in a mixed solvent of DMF and acetone with a volume ratio of 3:1 and magnetically stirred at room temperature for 10 h to obtain a TPU solution; among them, the mass concentration of TPU in the mixed solvent was 15%; Add the DMF dispersion of β-CD-TFN-1 to the TPU solution, stir at 10000 rpm for 60 min to obtain a homogeneous solution, and then prepare a TPU membrane in-situ doped with β-CD-TFN-1 by electrospinning; among them, β-CD-TFN-1 accounts for 5% of the mass of TPU. The specific steps of the electrospinning method are as follows: Carry out electrospinning using an electrospinning device. First, inject the homogeneous solution into a plastic syringe. The electrospinning conditions are: voltage 15 kV, injection speed 0.5 mL / h, receiving distance 10 cm, and continuous electrospinning for 2 h, that is, a TPU membrane in-situ doped with β-CD-TFN-1 is obtained on the collection roller. S3. Prepare a TPU nanocomposite membrane loaded with β-CD-TFN-1: Add β-CD-TFN-1 to DMF, stir and swell at 60 °C for 8 h, and then treat with an ultrasonic crusher (power 500 W, frequency 60 kHz) for 30 min to obtain a DMF dispersion of β-CD-TFN-1; among them, the mass concentration of β-CD-TFN-1 in DMF is 15%; among them, β-CD-TFN-1 accounts for 10% of the mass of TPU.

[0058] Put the TPU membrane in-situ doped with β-CD-TFN-1 obtained in S2 into the DMF dispersion of β-CD-TFN-1, stir evenly, then carry out vacuum filtration, wash with ethanol 3 times, and dry at 60 °C for 8 h to obtain a TPU nanocomposite membrane.

[0059] Comparative Example 9 A PAN nanocomposite membrane for removing PFAS in water, comprising the following preparation steps: S1. Prepare β-CD-TFN-1 according to Preparation Example 1; S2. Prepare a PAN membrane in-situ doped with β-CD-TFN-1 by electrospinning: Add β-CD-TFN-1 to DMF, stir and swell at 60 °C for 8 h, and then treat with an ultrasonic crusher (power 500 W, frequency 60 kHz) for 30 min to obtain a DMF dispersion of β-CD-TFN-1; among them, the mass concentration of β-CD-TFN-1 in DMF is 15%; Dissolve PAN in a mixed solvent of DMF and acetone with a volume ratio of 3:1 and stir magnetically at room temperature for 10 h to obtain a PAN solution; among them, the mass concentration of PAN in the mixed solvent is 15%; Add the DMF dispersion of β-CD-TFN-1 to the PAN solution, stir at 10000 rpm for 60 min to obtain a homogeneous solution, and then prepare a PAN membrane in-situ doped with β-CD-TFN-1 by electrospinning; among them, β-CD-TFN-1 accounts for 5% of the mass of PAN. The specific steps of the electrospinning method are as follows: electrospinning is performed using an electrospinning device, a homogeneous solution is first injected into a plastic syringe, and the spinning conditions are: voltage 15 kV, injection speed 0.5 mL / h, receiving distance 10 cm, and continuous spinning for 2 h, so that a PAN film doped with β-CD-TFN-1 in situ is obtained on a collecting roller; S3. Preparation of PAN nanocomposite membrane loaded with β-CD-TFN-1: β-CD-TFN-1 was added to DMF and stirred and swelled at 60°C for 8 hours, and then treated with an ultrasonic crusher (power of 500 W, frequency of 60 kHz) for 30 minutes to obtain a DMF dispersion of β-CD-TFN-1; wherein the mass concentration of β-CD-TFN-1 in DMF was 15%; wherein β-CD-TFN-1 accounted for 10% of the mass of PAN.

[0060] The PAN membrane in situ doped with β-CD-TFN-1 obtained in S2 was placed in the DMF dispersion of β-CD-TFN-1, stirred evenly, vacuum filtered, washed with ethanol three times, and dried at 60°C for 8h to obtain a PAN nanocomposite membrane.

[0061] Performance Test: Adsorption removal rate and adsorption efficiency: The TPU / PAN nanocomposite membranes for removing PFAS from water of Examples 1-6 and Comparative Examples 1-9 were placed in 50 mL of 100 μg / L PFOA, PFOS and PFBA aqueous solutions and allowed to stand for 2 h. Samples were then taken and the concentrations of the PFOA, PFOS and PFBA aqueous solutions were tested by HPLC to calculate the adsorption removal rates of PAOA, PFOS and PFBA.

[0062] The test results are shown in Table 1 below: Table 1

[0063] Comparing Examples 1-6 with Comparative Examples 1-9 in Table 1, it can be seen that for the TPU / PAN nanocomposite membrane for removing PFAS in water of the present invention, TPU and PAN are used as the base membranes for preparing the nanocomposite membrane. Due to the different flexibilities of the molecular chains and molecular weights of the two, they are entangled with each other in the system to form an interpenetrating network IPN structure, presenting a nanocomposite membrane base membrane with different pore sizes. Then, β-CD crosslinked by TFN is doped in situ therein, introducing cyclodextrin with adsorption function into the base membrane structure while obtaining a TPU / PAN membrane with hydrophobic effect. Finally, β-CD crosslinked by TFN is loaded on the surface of the TPU / PAN membrane to obtain the TPU / PAN nanocomposite membrane, so that the finally obtained TPU / PAN nanocomposite membrane has excellent adsorption capacities for long-chain PFAS and short-chain PFAS, with the adsorption removal rate of PFOA ≥ 97%, the adsorption removal rate of PFOS ≥ 96%, and the adsorption removal rate of PFBA ≥ 93%.

[0064] Comparing Examples 1-6 with Comparative Examples 1-2, 5 in Table 1, it can be seen that when uncrosslinked β-CD is added to the system, or when the ratio of TFN to β-CD is inappropriate during the crosslinking of β-CD by TFN, it will have an adverse effect on the adsorption capacity of the finally obtained TPU / PAN nanocomposite membrane for PFAS, especially the adsorption capacity for short-chain PFBA decreases. This may be because on the one hand, β-CD after TFN crosslinking forms continuous cyclodextrin cavities, and on the other hand, fluorinated hydrophobic segments are introduced, increasing the adsorption capacity for PFAS. At the same time, the crosslinked cyclodextrin is entangled with the molecular chains in the IPN structure of TPU / PAN, bringing different size distributions and pore sizes to the system, and the superposition of various effects improves the adsorption capacity of the nanocomposite membrane for PFAS.

[0065] Comparing Examples 1-6 with Comparative Examples 3-4 in Table 1, it can be seen that when the ratio of TPU to PAN in the system is inappropriate, the adsorption capacity of the finally obtained TPU / PAN nanocomposite membrane for PFAS will decrease to a certain extent. This may be because the formation of the IPN interpenetrating network and the entanglement of the molecular chains therein are related to the ratio of TPU to PAN, and the two need to be in a certain ratio to obtain a TPU / PAN membrane with a suitable pore size distribution.

[0066] Comparing Example 4 with Comparative Examples 6-7 in Table 1, it can be seen that when only β-CD crosslinked by TFN is doped in situ or only β-CD crosslinked by TFN is loaded, it will have an adverse effect on the adsorption capacity of the finally obtained TPU / PAN nanocomposite membrane for PFAS, especially the adsorption capacity for short-chain PFBA decreases significantly. It can be seen that in the TPU / PAN nanocomposite membrane, the in-situ doping and surface loading methods play a synergistic effect. This may be because adding crosslinked β-CD in different planar and three-dimensional dimensions at the microscopic level of the nanocomposite membrane has different effects on the adsorption capacity.

[0067] Comparing Examples 1-6 with Comparative Examples 8-9 in Table 1, it can be seen that when there is only TPU or PAN-based membrane in the system, the overall adsorption performance decreases significantly. This is because an interpenetrating network IPN structure is not formed in the system, and it does not have selectivity for PFAS with different molecular chain lengths, resulting in a decrease in the overall adsorption capacity.

[0068] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the embodiments of the present invention and are not intended to limit them. Although the embodiments of the present invention have been described in detail with reference to the preferred embodiments, those of ordinary skill in the art should understand that the technical solutions of the embodiments of the present invention can still be modified or equivalently replaced, and these modifications or equivalent replacements do not make the modified technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a TPU / PAN nanocomposite membrane for removing PFAS from water, characterized in that: The method comprises the following preparation steps: S1. Preparation of β-cyclodextrin-tetrafluoroterephthalonitrile polymer β-CD-TFN polymer: In an inert gas, β-cyclodextrin, tetrafluoroterephthalonitrile (TFN) and potassium carbonate are polymerized in DMF, and then washed, filtered and dried to obtain; In step S1, the weight ratio of β-cyclodextrin / tetrafluoroterephthalonitrile / potassium carbonate is (3-5):1:(4-6); S2. Preparation of TPU / PAN membrane in situ doped with β-CD-TFN polymer by electrospinning: The DMF dispersion of β-CD-TFN polymer was added to the TPU / PAN mixed solution, and the TPU / PAN membrane was prepared by electrospinning after obtaining a homogeneous solution after high-speed stirring; The mass ratio of TPU to PAN is (2-3): 1; In step S2, the β-CD-TFN polymer accounts for 5-15% of the total mass of TPU and PAN; S3. Preparation of TPU / PAN nanocomposite film loaded with β-CD-TFN polymer: The TPU / PAN membrane in situ doped with β-CD-TFN polymer obtained in S2 is added to the DMF dispersion of β-CD-TFN polymer, and after being stirred evenly, the membrane is filtered, washed and dried to obtain a TPU / PAN nanocomposite membrane; In the step S3, the β-CD-TFN polymer accounts for 5-15% of the total mass of TPU and PAN.

2. The method for preparing a TPU / PAN nanocomposite membrane for removing PFAS from water according to claim 1, characterized in that: The polymerization reaction temperature of step S1 is 85-95°C, and the reaction time is 12-18h; The inert gas is a nitrogen atmosphere or an argon atmosphere; The washing is performed by washing with hydrochloric acid for 3 times and then washing with deionized water for 3 times; The drying temperature is 80-100° C. and the drying time is 2-3 hours.

3. The method for preparing a TPU / PAN nanocomposite membrane for removing PFAS from water according to claim 1 or 2, characterized in that: The DMF dispersion of the β-CD-TFN polymer in step S2 is obtained by adding the β-CD-TFN polymer to DMF, stirring and swelling it, and then treating it with an ultrasonic crusher; The mass concentration of the β-CD-TFN polymer in DMF is 15%-20%; The stirring and swelling temperature is 60-80°C and the time is 6-8h; The power of the ultrasonic crusher is 300-500W, the frequency is 40-60kHZ, and the processing time is 30-60min; The TPU / PAN mixed solution is obtained by dissolving TPU and PAN in a mixed solvent of DMF and acetone and stirring to dissolve; The stirring and dissolving temperature is room temperature stirring, and the stirring time is magnetic stirring for 6-10h; The volume ratio of DMF to acetone is 3:1; The mass concentration of TPU / PAN in the mixed solvent is 15-25wt%; The high-speed stirring time is 30-60 min, and the stirring rate is 8000-1000 rpm; The specific steps of the electrospinning method are: electrospinning is performed using an electrospinning device, a homogeneous solution is first injected into a plastic syringe, and the spinning conditions are: voltage 15 kV, injection speed 0.5 mL / h-1 mL / h, receiving distance 10 cm-20 cm, and continuous spinning for 1-3 hours, so that a TPU / PAN film in situ doped with β-CD-TFN polymer is obtained on a collecting roller.

4. The method for preparing a TPU / PAN nanocomposite membrane for removing PFAS from water according to claim 1 or 2, characterized in that: The DMF dispersion of the β-CD-TFN polymer in step S3 is obtained by placing the β-CD-TFN polymer in DMF, stirring and swelling it, and then treating it with an ultrasonic crusher; The stirring and swelling temperature is 60-80°C, and the time is 6-8h; the power of the ultrasonic crusher is 300-500W, the frequency is 40-60kHZ, and the processing time is 30-60min; The filtration is vacuum filtration; the washing is ethanol washing; The drying is performed at 50-60° C. for 8-12 hours.

5. A TPU / PAN nanocomposite membrane for removing PFAS from water, characterized in that: The TPU / PAN nanocomposite film is prepared by the preparation method described in any one of claims 1 to 4.

6. The TPU / PAN nanocomposite membrane for removing PFAS from water according to claim 5, characterized in that: The TPU / PAN nanocomposite membrane for removing PFAS in water has an adsorption removal rate of ≥97% for PFOA, an adsorption removal rate of ≥96% for PFOS, and an adsorption removal rate of ≥93% for PFBA.

7. An application of a TPU fiber membrane prepared by the method for preparing a TPU / PAN nanocomposite membrane for removing PFAS from water according to any one of claims 1 to 4, wherein the application is to remove PFAS from water.

Citation Information

Patent Citations

  • Organic fluorine-based-compound adsorbent comprising cyclodextrin-supporting polymer

    CN104853841A

  • Nanofiber membrane for removing short-chain PFASs in water as well as application and regeneration method of nanofiber membrane

    CN117138761A

  • Alkali-resistant polymer MBR membrane and preparation method thereof

    CN118022551A

  • TPU (thermoplastic polyurethane) fiber membrane for removing bisphenol substances in water and preparation method of TPU fiber membrane

    CN118847071A

  • Membrane modified hydrogels, process for their manufacture and their use as active agent dispenser

    EP0046136A2